2012
DOI: 10.1063/1.4739282
|View full text |Cite
|
Sign up to set email alerts
|

Influence of transverse fields on domain wall pinning in ferromagnetic nanostripes

Abstract: We report an experimental study dealing with the influence of in-plane transverse fields on the domain wall (DW) pinning in ferromagnetic nanostripes. We analyzed the pinning probability and depinning fields for several fabrication induced pinning sites. For all measurements reported here, the depinning field decreases with increasing transverse field independently from the actual domain wall type and the shape of the pinning site. The pinning probability decreases with increasing transverse fields for weak pi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 32 publications
0
3
0
Order By: Relevance
“…Benefiting from the current micro- and nanofabrication techniques, each GMR biosensor is typically in the size of tens to hundreds of micrometers. As shown in Figure , theoretically, GMR biosensors could be scaled to more than 1 million sensors/cm 2 . , To date, different GMR biosensor patterns have been reported, for example, a stripe shape , (Figure A), a spiral shape , (not shown), a meander shape (Figure B), large-area (Figure C), and a “U” shape (Figure D). It is reported that for GMR-based bioassays, the MNP labels landing at the sensor edges cause larger signal differences compared to the same MNP labels landing on top of the sensor .…”
Section: Gmr Biosensor Designsmentioning
confidence: 99%
“…Benefiting from the current micro- and nanofabrication techniques, each GMR biosensor is typically in the size of tens to hundreds of micrometers. As shown in Figure , theoretically, GMR biosensors could be scaled to more than 1 million sensors/cm 2 . , To date, different GMR biosensor patterns have been reported, for example, a stripe shape , (Figure A), a spiral shape , (not shown), a meander shape (Figure B), large-area (Figure C), and a “U” shape (Figure D). It is reported that for GMR-based bioassays, the MNP labels landing at the sensor edges cause larger signal differences compared to the same MNP labels landing on top of the sensor .…”
Section: Gmr Biosensor Designsmentioning
confidence: 99%
“…[21][22][23][24] The ability of the transverse field to change the domain wall speed also impacts the ability of a notch to trap a domain wall, in that fast moving walls can pass a notch that is capable of trapping a slower moving wall. [25][26][27] When the transverse field component is applied parallel to the direction of the magnetic moments within the domain wall, it will speed up, and if applied anti-parallel, it will slow down. 22 Similarly in Fig.…”
mentioning
confidence: 99%
“…In general, it has been shown that the speed of a current-driven DW can be increased by either improving the driving force from the current or by enhancing the DW fidelity (i.e. its rigidity) [52][53][54][55][56][57][58][59][60][61], which is a measure of how strong the DW can resist a structural change upon the application of external stimuli. configuration for various strength of external transverse field.…”
Section: Magnetic Domain Wallsmentioning
confidence: 99%